Emigracja i diaspora w dyskursie politycznym w Polsce w latach 1991-2015 - Magdalena Lesińska (University of Warsaw, Centre of Migration Research (CMR), 2015)
– The text analyzes the political discourse in Poland for the presence of the topic of emigration and diaspora. The study is a qualitative content analysis, the subject of the analysis are programs of political parties, materials and documents created for election campaigns and exposé of prime ministers, forming successive governments. The analysis covers the period from election 1991 to the 2011-2015 parliamentary term. A more detailed analysis covers the years 2005-2011, the period after the Polish accession to the EU, symbolizing the beginning of the last wave of mass emigration. The main research questions concern the space, form and the recipients of political message on the theme of emigration and diaspora, its changes over time and the relationship between the declarations contained in the political parties programs, prime ministers exposé and later in government initiatives. The analysis showed that subjects relating to emigration and diaspora were present (though to varying degrees) during each election campaign, and the greatest interest in them took place during the elections in 2007. These topics were also not the subject of political controversy: the various political parties were rather consistent in the diagnosis of the situation and the solutions proposed in the programs, government initiatives on emigration and Poles living abroad met with symbolic resistance from the political opponents.
Keywords: 330; emigration; Polish diaspora; political discourse; political programs and parties